Functionally impaired RPL8 variants associated with Diamond–Blackfan anemia and a Diamond–Blackfan anemia‐like phenotype. Issue 3 (23rd January 2022) - Lebaron, Simon; O'Donohue, Marie‐Françoise; Smith, Scott C.; Engleman, Kendra L.; Juusola, Jane; Safina, Nicole P.; Thiffault, Isabelle; Saunders, Carol J.; Gleizes, Pierre‐Emmanuel
Abstract: Diamond–Blackfan anemia is a rare genetic disease characterized by erythroblastopenia and a large spectrum of developmental anomalies. The vast majority of the cases genetically described are linked to heterozygous pathogenic variants in more than 20 ribosomal protein genes. Here we report an atypical clinical case of DBA associated with a missense variant in RPL8, which encodes RPL8/uL2, a protein of the 60S large ribosomal subunit. RPL8 has been previously implicated as a candidate disease gene in one patient with DBA bearing another type of missense variant; however, evidence for pathogenicity was limited to computational tools. Using functional studies in lymphoblastoid cells as well as yeast models, we show that the RPL8 variants detected in these two patients encode functionally deficient proteins that affect ribosome production and are therefore likely pathogenic. We propose to include RPL8 in the list of DBA‐associated genes. Abstract : RPL8 variants linked to Diamond‐Blackfan anemia or a related syndrome impair ribosome synthesis.